2022
DOI: 10.3389/fimmu.2022.843059
|View full text |Cite
|
Sign up to set email alerts
|

SLAMF Receptor Expression Identifies an Immune Signature That Characterizes Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease of unknown etiology, linked to alterations in both the innate and the adaptive immune system. Due to the heterogeneity of the clinical presentation, the diagnosis of SLE remains complicated and is often made years after the first symptoms manifest, delaying treatment, and worsening the prognosis. Several studies have shown that signaling lymphocytic activation molecule family (SLAMF) receptors are aberrantly expressed and dysfunctional in SLE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Genetic loci encoding the SLAMF genes are associated with SLE risk, particularly polymorphisms in SLAMF3, SLAMF4, and SLAMF6 (1-3). However, only small differences in cell surface SLAMF expression levels have been described in SLE compared to controls, which are not consistently seen across studies (4)(5)(6). We found that SLAMF3 and SLAMF6 expression can be detected on 98% of circulating T cells in SLE and healthy controls (7).…”
Section: Introductioncontrasting
confidence: 61%
“…Genetic loci encoding the SLAMF genes are associated with SLE risk, particularly polymorphisms in SLAMF3, SLAMF4, and SLAMF6 (1-3). However, only small differences in cell surface SLAMF expression levels have been described in SLE compared to controls, which are not consistently seen across studies (4)(5)(6). We found that SLAMF3 and SLAMF6 expression can be detected on 98% of circulating T cells in SLE and healthy controls (7).…”
Section: Introductioncontrasting
confidence: 61%
“…Upregulated LY9 and LY108 expression in T cells from SLE patients was found to serve as a major costimulus for Th17 differentiation and IL-17 production [ 34 ]. Using single-cell mass cytometry to identify the expression of all SLAMF receptors on SLE PBMCs, Humbel, Bellanger [ 35 ] found that naïve B cells coexpressing SLAMF1 and LY9 and switch memory B cells coexpressing SLAMF1, LY9, SLAMF5 and SLAMF6 were significantly increased in SLE patients. However, the expression of LY9 in total B cells showed no significant difference between SLE patients and HCs.…”
Section: Discussionmentioning
confidence: 99%
“…62 63 70 74 75 80 Important immune pathways were identified including extrafollicular B cell involvement, 54 DNA methylation, 65 expansion of major helper T cell subsets and unique proliferating (Ki-67+) immune cell subsets, 76 and signalling lymphocytic activation molecule family receptors on peripheral blood mononuclear cells. 64 Diagnostic models SLE diagnostic models were used to identify patients with SLE compared with healthy controls and from other autoimmune rheumatic diseases (eg, rheumatoid arthritis, Sjögren disease, systemic sclerosis, multiple sclerosis), Kikuchi disease and other forms of nephropathy for LN reports 23…”
Section: Pathogenesismentioning
confidence: 99%